RESIKO SISTEMATIS DAN TINGKAT KEUNTUNGAN SAHAM DI PASAR MODAL - Yohanes Suharsana (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2010)
Capital Market is one of effective tools in fastening the reconstruction of a state.It is causedby capital market is a conscription of a long range fund from society to be distributied to theproductive sector. A capitalist that will invest fund in capital market, must take a considerationberween the risk and the adventage that is expected from the investment.While the purpose of this research are to know how big the systematic risk and profit levelthat is expectsd, to know the correlation between the systematic risk and the profit level that isexpected.From the result we are able to significant relationship between systematic risk and theprofit level. It shows that the bigger systematic risk the bigger also to the profit level. Vice verse. Byforming portofolio namely combination of high stock systematic risk () and low stock systematic risk(). This combined is expected to form the efficient portofolio.